Ustaz Selebriti di YouTube: Pendidikan Islam Moderat dan Toleransi Antarumat Beragama Mahasiswa - Mas Teguh Wibowo; Salminawati; Zaini Dahlan (Journal of Islamic Education Students (JIES), 2026)
This study examines students’ reception of celebrity ustaz preaching on YouTube in relation to moderate Islamic education and interreligious tolerance. The study focuses on how Ustaz Abdul Somad, Ustaz Adi Hidayat, and Habib Husein Ja’far Al Hadar construct messages of moderation and tolerance, as well as how UINSU students interpret these messages as active digital audiences. This research employed a qualitative approach with a netnographic method. Data were collected through observation of selected YouTube preaching content, semi-structured interviews with eight students from Islamic-based faculties at UINSU, and documentation of relevant digital materials. Data were analyzed through coding, thematic categorization, and netnographic interpretation by connecting digital content with students’ offline religious experiences. The findings show that the three celebrity ustaz construct moderate Islamic education and tolerance messages through normative-ethical, educational-argumentative, and dialogical-inclusive communication patterns. The novelty of this study lies in its integration of digital da’wah content analysis and students’ audience reception, showing that YouTube functions not only as a preaching medium but also as a space for shaping students’ religious understanding, digital religious literacy, and interreligious tolerance.